The factors that influence the acceptance of Ar-Rahnu among Wangsa Maju Residents / Umi Kalthum Muhammad Nosskah - Muhammad Nosskah, Umi Kalthum (Faculty of Business and Management, 2019)
Ar-Rahnu is also known as Islamic Pawnbroking, which referring to short term collateralize borrowing. Ar-Rahnu is the best alternative for pawnbroking service for borrowers based on Shariah principle. The development of Ar Rahnu in Malaysia by using the Islamic contract such as Qardul Hasan, Ar Rahnu , Al-Wadiah and Al-Ujrah. It is a convenience form of credit financing in Malaysia. Cheong & Sinnakkannu (2012) stated about Ar-Rahnu and conventional pawnbroking where is borrowers more prefer in using conventional financing which they can borrow up to 90 percent to 100 percent without pledged any assets as collateral. This study objective is to review the factors that influencing the acceptance of Ar-Rahnu among Wangsa Maju residents. This study used a quantitative method which utilised the survey method by using questionnaires to 150 respondents of Wangsa Maju residents. The questionnaire were combination of several previous studies. The dependent variable is factor that influence the acceptance of Ar Rahnu, while the independent variables are Shariah View, Customer service, Locality and Pledged assets. As for the result, it can be concluded that there is significant relationship between the factor that influence the acceptance of Ar Rahnu with Shariah View and Customer service. Meanwhile Locality and Pledge assets shows no significant relationship with the acceptance of Ar-Rahnu among Wangsa Maju residents.